Carte de L'AmeÌrique Septentrionale - Lapie, M. (Pierre), 1779-1850 (Eymery Fruger et Cie., 1830)
Map shows major cities along the coasts of North America, Central America, and the Antilles. Native American habitation in some areas of North America are also noted. Inset: "Bering Sea and the Aleutien Islands." Relief shown by hachures. No scale noted.